THU0310 OPTIMAL INITIAL DOSE OF GLUCOCORTICOID FOR ELDERLY-ONSET ANCA ASSOCIATED VASCULITIS: SAFTY OUTOCOME ANALYSIS OF TWO NATIONWIDE, PROSPECTIVE, INCEPTION COHORT STUDIES. (June 2019) - Ohashi, Keiji; Sada, Kenei; Asano, Yosuke; Hayashi, Keigo; Asano, Sumie Hiramatsu; Yamamura, Yuriko; Morishita, Michiko; Watanabe, Haruki; Narazaki, Mariko; Matsumoto, Yoshinori; Kawabata, Tomoko; Wada, Jun; et al.
Abstract : Background: Glucocorticoid (GC) is still the mainstay of treatment for antineutrophil cytoplasmic antibody (ANCA) -associated vasculitis (AAV) while GC use, disease severity, and older age are risk factors for accrual of damage and infection in AAV 1)2) . Objectives: To explore optimal initial dose of GC for patients with elderly-onset AAV based on safety outcome analysis using data from two nationwide prospective inception cohort studies (RemIT-JAV and RemIT-JAV-RPGN). Methods: RemIT-JAV and RemIT-JAV-RPGN enrolled consecutive patients with newly diagnosed AAV fulfilling the criteria for primary systemic vasculitis as proposed by the European Medicines Agency algorithm and requiring immunosuppressive treatment. From the cohort studies, elderly-onset (≥65 years) patients with microscopic polyangiitis and granulomatosis with polyangiitis, classified as generalized or severe disease type according to the European Vasculitis Study Group-defined disease severity, were enrolled in this analysis. The primary outcome measures were Vasculitis Damage Index (VDI) at 24 th month and serious infections during 2 years after starting treatment for AAV. The patients were divided into three groups based on initial dose of GC: high-dose (HD) group, prednisolone (PSL) ≥0.8 mg/kg/day; medium-dose group (MD), 0.6≤ PSL <0.8 mg/kg/day; low-dose (LD) group, PSL <0.6 mg/kg/day. The VDI were classified into treatment-related VDI 1) and disease-related VDI (excluding treatment-related VDI from total VDI). We evaluated associations between initial GC dose and the primary outcomes. Results: Of 477 patients registered in the original cohort studies, 161 patients were enrolled in the present study. Mean age (± SD) were 74 (± 5) in HD group, 74 (± 5) in MD group, and 78 (± 6) years in LD group, respectively. There was no significant difference in sex, disease severity, type of ANCA, C-reactive protein levels at baseline, Birmingham Vasculitis Activity Score at baseline, remission rates, and relapse rates. HD group exhibited significantly lower creatinine levels at baseline than MD and LD groups (216 ± 207 in HD, 339 ± 263 in MD, 331 ± 301 μmol/L in LD, respectively; p = 0.0012). Proportion of concomitant cyclophosphamide use during 90 days after starting treatment for AAV decreased (58% in HD, 36% in MD, and 15% in LD, respectively; p <0.0001) while disease activity-related VDI at 24 th month increased (2.09 ± 1.39 in HD, 2.54 ± 1.16 in MD, and 2.83 ± 1.60 in LD, respectively; p = 0.018) as the initial GC dose went down. HD group developed serious infections more frequently than MD and LD groups (25/65 [38%] in HD, 10/50 [20%] in MD, 9/46 [20%], respectively; p = 0.033). Conclusion: Based on safety outcome analysis, 0.6 ≤ PSL <0.8 mg/kg/day might be optimal initial dose of GC for treatment of elderly-onset patients with AAV. References: [1] Robson J, et al. Rheumatology (Oxford). 2015 Mar;54(3):471-81. [2] Watanabe-Imai K, et al. Mod Rheumatol. 2017 Jul;27(4):646-651. Disclosure of Interests: Keiji Ohashi: None declared, KENEI SADA Speakers bureau: Ken-Ei Sada received speaker honoraria from Chugai., Yosuke ASANO: None declared, Keigo Hayashi: None declared, Sumie Hiramatsu Asano: None declared, Yuriko Yamamura: None declared, Michiko Morishita: None declared, Haruki Watanabe: None declared, Mariko Narazaki: None declared, Yoshinori Matsumoto: None declared, Tomoko Kawabata: None declared, Jun Wada Grant/research support from: Jun Wada received grant support from Astellas, Bayer, Chugai, Daiichi Sankyo, Kissei, Kyowa Hakko Kirin, MSD, Otsuka, Teijin, Torii, Pfizer, Takeda, and Taisho Toyama., Speakers bureau: Jun Wada received speaker honoraria from Astellas, Boehringer Ingelheim, Novartis, and Tanabe Mitsubishi., masayoshi harigai Grant/research support from: Tokyo Women's Medical University (TWMU) has received unrestricted research grants for Division of Epidemiology and Pharmacoepidemiology of Rheumatic Diseases from Ayumi Pharmaceutical Co. Ltd., Bristol Meyers Squib, Chugai Pharmaceutical Co. Ltd., Nippon Kayaku Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Corp., and with which TWMU paid the salary of MH. MH has also received research grants from AbbVie Japan GK, Eisai Co. Ltd., Takeda Pharmaceutical Co., Ltd., and Teijin Pharma Ltd., Hirofumi Makino Consultant for: Hirofumi Makino is a consultant for AbbVie, Boehringer-ingelheim and Teijin Pharma., Speakers bureau: Hirofumi Makino receives speaker honoraria from Boehringer-ingelheim (less than $10, 000 each).